Answer :

LCM = x3 – 6x2 + 3x + 10

= x3 – 5x2 - x2 + 3x + 10


= x2(x – 5) – (x2 – 3x – 10)


= x2(x – 5) – (x2 – 5x + 2x – 10)


= x2(x – 5) – (x(x – 5) + 2(x – 5))


= x2(x – 5) – (x + 2) (x – 5)


= (x – 5) [x2 – x -2]


= (x – 5) [x2 – 2x + x -2]


= (x – 5) [x(x – 2) +1(x – 2)]


= (x – 5) (x – 2) (x + 1)


Since HCF = (x + 1) it belongs to both the polynomials.


So u(x) = (x + 1) (x – 5)


= x2 – 4x - 5


So v(x) = (x + 1) (x – 2)


= x2 – x - 2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If u(x) = (x – 1)Rajasthan Board Mathematics

Find the lowest cRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics

The area of a recRajasthan Board Mathematics

The LCM and HCF oRajasthan Board Mathematics

If α and β are thRajasthan Board Mathematics

Find the zeroes oRajasthan Board Mathematics

Write ShridharachRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics